Microwave assisted hydrothermal synthesis of flower shaped bismuth sulfide nanomaterial and its usage for copper removal from spiked tap water samples - Tezgin, Emine; Bozyigit, Gamze Dalgic; Zaman, Buse Tugba; Serbest, Hakan; Turak, Fatma; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2026)
This study was designed to enhance the removal efficiency of copper ions from tap water samples by developing an adsorptive treatment method employing bismuth sulfide based nanoflowers (Bi2S3 NFs) and evaluating with the flame atomic absorption spectrophotometry (FAAS) system. A fast, and easy microwave assisted hydrothermal method was developed to synthesize Bi2S3 NFs for this application. The equilibrium adsorption investigations were conducted in tap water samples following the full optimization of all experimental parameters through univariate optimization research. As the result of optimization studies, the removal process was conducted in the conditions of 30 mg of Bi2S3 NFs for 40 mL of aqueous copper solution which was adjusted to pH 7.0 with 2.0 mL of buffer solution. The adsorption process was enhanced utilizing a sonication bath for 2.0 min before the effluent separation. The removal efficiency values, expressed as percentages, were found to be between 83.8 and 98.9% for various concentrations of copper ions in the tap water samples. Langmuir adsorption isotherm was used to model the equilibrium data. Equilibrium constant of Langmuir was calculated as 5.887 L/mg. The results obtained indicate that the adsorption mechanism of Bi2S3 NFs, when used as adsorbents, is effective to remove copper from tap water samples.
Keywords: Copper; Flame atomic absorption spectrometry; Bismuth sulfide nanoflowers; Linear adsorption isotherms; Treatment strategies; WASTE-WATER; ADSORPTION; ADSORBENT; CU(II); FE3O4; IONS; Chemistry